ANALYSIS OF UNCONTROLLED REACTIVITY INSERTION TRANSIENT OF TRIGA MARK 2000 BANDUNG USING MTR PLATE TYPE FUEL ELEMENT - Surian Pinem; Tukiran Surbakti; Imam Kuntoro (Website, 2020)
ANALYSIS OF UNCONTROLLED REACTIVITY INSERTION TRANSIENT OF TRIGA MARK 2000 BANDUNG USING MTR PLATE TYPE FUEL ELEMENT. Analysis of uncontrolled reactivity insertion is very important for the safety of reactor operations. Determination of melting point limit, critical heat fluxes and melting temperatures of cladding are the main objectives for most of these studies to determine whether fuel temperature can withstand the transient insertion of reactivity. In this study, uncontrolled reactivity insertion transient was carried out due to the withdrawal of control rods in nominal power of 1 MW and 2 MW. Analysis of reactivity transient was carried out using the WIMSD/5B and MTRDYN codes. The WIMSD/5B code is used to generate cross sections and the MTRDYN program is used for analysis under transient conditions. Based on calculations on the initial power of 1 MW and 2 MW with an insertion of reactivity of greater than 0.5 /s the reactor operation is not safe because the fuel temperature exceeds the design limit. For reactivity insertion 0.5 /s allows increased power can be stabilized by feedback reactivity. For 1 MW of nominal power, the maximum coolant temperature, cladding and fuel are 86.39 oC, 164.86 oC and 165.33 oC, respectively. For 2 MW of nominal power, the maximum coolant temperature, cladding and fuel are 89.09 oC, 176.96 oC and 177.602 oC, respectively. Based on calculation, It is concluded that the feedback mechanism can protect the fuel cladding from a local meltdown if reactivity insertion 0.5 /s and the reactor is in nominal power of 1 MW and 2 MW.